The Healing Properties of Woodfordia Uniflora (A.Rich.) Koehne from the Dhofar Region of Oman Against Ulcers and Clostridium Perfringens Infections - Cock, Ian Edwin; Rashan, Luay (AIJR Abstracts, 2026)
Gangrene is a serious condition, which is characterised by tissue death. It results from restricted blood flow and anoxic conditions and is frequently caused by atherosclerosis, tissue damage, diabetes mellitus and some pathogen infections. Gas gangrene (clostridial myonecrosis), a common class of gangrene, results from bacterial (particularly Clostridium perfringens) infections following tissue injury. Woodfordia uniflora is used in traditional Arabian healing systems to treat gangrene ulcers and skin sores. However, despite its well-documented uses, W. uniflora has not yet been rigorously tested against bacterial causes of gangrene ulcers and skin sores. Additionally, W. uniflora extracts are yet to be tested for therapeutic potential against other aspects of ulcer/wound healing, including inflammation and tissue regeneration. Solvent extracts prepared from W. uniflora leaves were tested against C. perfringens as well as a panel of epidermal bacteria. Antimicrobial activity was quantified by MIC determination. The anti-inflammatory activity of the extracts was evaluated using COX-2 and PGE2 ELISA assays. Toxicity was evaluated using ALA and HDF cell viability bioassays. The methanolic, ethanolic and aqueous extracts displayed noteworthy inhibitory activity (≤875µg/mL) against C. perfringens. The ethanol extract was particularly good, with an MIC of 250µg/mL. The extracts also had noteworthy inhibitory activity against several antibiotic-resistant epidermal bacteria, including MRSA (MICs 250-650µg/mL). Additionally, the W. uniflora extracts (1.25mg/mL) significantly inhibited COX-2 activity and PGE2 secretion. The ethanol extract was particularly promising, decreasing COX-2 enzymatic activity and PGE2 secretion by approximately 60% and 73% respectively. All W. uniflora extracts were non-toxic in the ALA and HDF cell viability assays, indicating their safety for therapeutic use. Taken together, these results indicate that W. uniflora extracts have therapeutic potential in the treatment of gas gangrene by inhibiting C. perfringens (and several skin bacteria), as well as inhibiting COX-2 mediated inflammation. Further studies are required to determine whether the extracts also affect extracellular matrix formation and tissue remodeling, and to identify the extract components responsible for those activities.
Keywords: Botanique -- Oman

Exploring the Effectiveness of Omani Frankincense Boswellia Sacra Oleo-Gum Resin Extracts and Essential Oils Against the Parasite Causing Cystic Echinococcosis Invitro Effect - Ramadhan, Baraa Basil; Abdulazeez, Asmaa; Rashan, Luay (AIJR Abstracts, 2026)
Cystic echinococcosis (CE) is a life threating disease and a major public health problem caused by the larval stage of the tapeworm named Echinococcus granulosus. Cystic echinococcus is transmitted from animals to human (zoonotic disease). In endemic areas, the incidence rate reaches over 50 per 100,000 person/year and prevalence may be as high as 5-10%. It is found in most countries worldwide, but it is not an epidemic disease. Current treatment involves surgical removal of the cysts, percutaneous drainage, or chemotherapy with anthelmintic drugs like albendazole. While albendazole is effective in treating (CE) in both humans and animals, though, it has drawbacks, including poor absorption, vertigo, liver enzymes elevations plus the risk of recurrence. Recently, there was a high tendency among researchers to evaluate and present herbal plants as an alternative option due to being easily available, inexpensive, cheap and with low side effects. Therefore, the current project aims to explore the scoliocidal potential of Boswellia sacra extracts, and essential oils on Echinococcus granulosus both in vitro and in vivo. Protoscolices were collected from hydatid cysts obtained from infected sheep livers. Many polar and non-polar solvents were used to obtain a wide range of extracts from B. sacra gum resin. Extracts were prepared and applied at various concentrations (e.g. 30, 3, 0.3 µg/ml) for different exposure times (2-60 minutes). The mortality rates were assessed using 0.1% eosin staining by light microscopy. The results so far obtained indicate that all extracts used in the current study displayed promising significant scoliocidal effects against E. granulosus in vitro speaking. However, the standardized B. sacra gum resin extract showed the highest scoliocidal activity in vitro, achieving 100% mortality at 3µg/ml after 10 minutes of exposure compared to both negative and treated positive control with albendazole. These results are promising, however, additional in vivo studies are in progress to confirm such activity.
Keywords: Botanique -- Oman

Antimicrobial and Antifungal Activity of Standardized Omani Frankincense Extract Powder - Dobretsov, Sergey; Al-Naamani, Laila; Rashan, Luay (AIJR Abstracts, 2026)
Frankincense, the aromatic resin obtained from Boswellia species, has been traditionally valued for its medicinal and antimicrobial properties. A standardized extract of Boswellia sacra (Omani frankincense) was evaluated for its antimicrobial and antifungal properties. The chemical composition of the powder was analyzed using HPLC/MS, revealing a rich profile of bioactive triterpenoids including boswellic acids (AKBA, KBA, α-BA, β-BA, α-ABA, and β-ABA) and lupeolic acids (LA and ALA). Among these, β-ABA (86 µg/mg) and AKBA (50 µg/mg) were the most abundant. Antibacterial activity was assessed using minimum inhibitory concentration (MIC) assays, showing moderate inhibition of Escherichia coli (MIC: 512 mg/mL) and Staphylococcus aureus (MIC: 1024 mg/mL). Antifungal testing revealed stronger effects, with 38% inhibition of Fusarium sp. at 0.25 mg/mL after 5 days of incubation. However, the inhibition of Alternaria alternata at 0.5 mg/mL was 45%. These results support the potential of this standardized extract as a natural antimicrobial and antifungal agent and underscore the value of Omani frankincense in traditional and modern therapeutics.
Keywords: Botanique -- Oman

The Combined Effect of Nerium Oleander Cold Leaf Extract and Some Selected Omani Frankincense Boswellia Sacra Oleo-Gum Resin on the Parasite Causing Cystic Echinococcosis Invitro Effect - Yasin, Huda Fawaz; Ali, Asmaa Abdulazeez; Rashan, Luay (AIJR Abstracts, 2026)
Cystic echinococcosis (CE) is a severe zoonotic disease that poses a significant threat to humans and animals, slow animal husbandry, caused by larval stages of Echinococcus granulosus. Canines are the definitive host, while humans are the accidental host. E. granulosus infections often remain asymptomatic for years before the cysts grow large enough to cause symptoms. Hepatic and pulmonary signs and symptoms are the most common clinical manifestations. Approximately 4 million people are infected with hepatic hydatid disease globally, and an additional 60 million are at risk of infection. The liver is the most involved organ, although it may affect other organs. The diagnosis of cystic echinococcosis relies on immunodiagnostic methods alongside radiological methods in combination with clinical findings. Albendazole and Mebendazoles are the drugs for choice in treating small cysts and preventing recurrence after surgery. In general, herbal extracts from different plants have gained attention in recent years for the prevention and treatment of a variety of chronic conditions due to their multi-targeted characteristics. Nerium oleander has a wide range of potential activities including anticancer, antibacterial and anti-inflammatory properties. B. sacra gum resin possesses a wide range of potential activities such as anti-cancer, anti-inflammatory, anti-asthmatic, analgesic, immunomodulatory. Given the side effects of the medications used and the risks of surgical procedures, the present study aimed to investigate the effect of combining extracts of N. oleander leaves and selected B. sacra gum resin extracts. The samples were exposed for different time periods (5-20-35-50) minutes using different concentrations (30µg/ml-3µg/ml-0.3µg/ml) for each exposure period. The combination of the extracts had a clear effect on the percentage of killing protoscoleces in vitro. The percentage of killing protoscoleces increased with increasing concentration and exposure period of the extracts in vitro, the highest percentage of killing was recorded in the N. oleander extract, reaching 70% at a concentration of 30mg/ml for a 50-minute exposure period. After combining the extracts, the highest percentage of killing was recorded, reaching 64% at a concentration of 30mg/ml for a 50-minute exposure period. The highest percentage of killing was recorded for the B. sacra extracts reaching 58% at a concentration of 30mg/ml for a 50-minute exposure period. The current results in vitro are interesting and encouraging, indicating some synergistic effect between these extracts, however, additional animal studies are required to further validate the synergistic effect of B. sacra and Nerium oleander leaves.
Keywords: Botanique -- Oman